Keputusan Penggunaan BSI Mobile Ditinjau dari Kemudahan, Kemanfaatan dan Keamanan Fitur Layanan pada Generasi Milenial di Wilayah Solo Raya - Fuad Hasyim; Sherly Oktaviana; Desila Putri (Jurnal BAABU AL-ILMI: Ekonomi dan Perbankan Syariah, 2023)
Raya area still choose to use conventional bank services and have not yet used Islamic bank services.  This study aims to determine the effect of convenience, benefit and security variables on the use of BSI Mobile.  The sampling technique used clustered and random sampling methods.  The population obtained from each region is 1,412,000 people, resulting in a minimum sample size of 107 respondents.  Analysis of the research data using multiple linear regression analysis.  The results of this study show that the convenience and benefit variables significantly influence the decision to use the mobile banking, while the security variables does not affect the decision to use BSI Mobile